Larvae of Neotropical Helochares Mulsant (Coleoptera, Hydrophilidae): Description of H. femoratus (Brullé) - Fernandez, Liliana Alicia (2004)
Egg case and larvae of Helochares femoratus (Brullé) are described from Ensenada, Buenos Aires Province, Argentina. Diagnostic characters of external morphology are discussed, and comparisons with other known species of Helochares Mulsant are made. A key to different larval instars is provided.